TEACHERS’ BELIEFS ABOUT TEACHING READING IN A SECONDARY SCHOOL IN LITHUNIA - Smilgienė, Silvija (Verbum, 2015)
The beliefs teachers hold are acknowledged to shape their classroom practice and influence the achievements of their students. Understanding the beliefs of teachers is significant to improve pre-service and in-service teacher development programmes and to increase the teaching quality. In this study teachers’ beliefs are approached as social, dynamic and context-bounded entities that are constructed through social interaction (Woods, 2006). This case study investigated English language teachers’ beliefs about teaching reading in a secondary school in Lithuania. The goal of the study was to understand teachers’ beliefs about their students’ needs when teaching reading and what reading methods teachers use to meet those needs. The study also aimed to explore the extent to which a small sample of teachers’ believed they met their students’ needs. The findings revealed that most of the interviewed teachers’ beliefs about the reading process were conceptualized in terms of lexical and grammatical knowledge. However, their beliefs about classroom practice revealed that teachers used multiple methods to teach reading and viewed the teaching of reading as an interactive, social and process-oriented event. These beliefs originated from practice and allowed inferences to be made that beliefs about reading development were not completely consistent with beliefs about how to teaching reading. Finally, the study identified that teachers share the belief that they lacked sufficient knowledge of how to meet the reading needs effectively of their students and this seemed to impact on how they constructed their identities as teachers. The given data suggest that the interviewed teachers’ theoretical beliefs about reading development are at variance with their personal beliefs of how to teach reading. The variation in the beliefs of these teachers originates from several context-bounded sources such as the requirements of exams, personal experiences of teachers, and learners’ needs.